Privacy Remedies - Scholz, Lauren H (2019)
When consumers sue companies for privacy-intrusive practices, they are often unsuccessful. Many cases fail in federal court at the motion to dismiss phase because the plaintiff has not shown the privacy infringement has caused her concrete harm. This is a symptom of a broader issue: the failure of courts and commentators to describe the relationship between privacy rights and privacy remedies. This Article contends that restitution is the normal measure of privacy remedies. Restitution measures relief by economic gain to the defendant. If a plaintiff can show the likely ability to recover in restitution, that should be sufficient to pass muster at the motion to dismiss phase even if the court is unconvinced that the plaintiff could show a case for compensatory damages flowing from harm. This argument intervenes in the scholarly literature in two ways. First, it supports the realist perspective that remedies are constitutive of rights. The election of restitution as a remedy suggests that privacy should be conceptualized in tort as quasi-property, and that contract and/or restitution claims should be a standard part of privacy infringement pleadings. Second, it challenges the view that defining specific and stronger privacy rights at law would be sufficient to increase privacy protection. If any privacy rights are to exist at all, they must be linked to proportional, accessible remedies